AT1 receptor antagonism promotes bone loss attenuation in experimental periodontitis, blocks inflammatory mediators, and upregulates antioxidant enzymes and bone formation markers - Dionísio, Thiago J.; Souza, Gabriela P.; Colombini-Ishikiriama, Bella L.; Garbieri, Thais F.; Parisi, Viviane A.; Oliveira, Gabriela M.; Cano, Isadora P.; Rodini, Camila O.; Oliveira, Sandra H. P. [UNESP]; Greene, Andrew S.; Santos, Carlos F. (Wiley, 2020)
Background: The initiation and progression of periodontitis might involve a local renin-angiotensin system in periodontal tissue. This study hypothesized that Losartan treatment could promote protection to rats submitted to experimental periodontitis (EP) by attenuating alveolar bone loss due to reduction in inflammatory cytokines, better reactive oxidant species regulation and maintenance of the balance between bone formation and resorption factors. Methods: One hundred and thirty rats were submitted to EP with a silk suture thread (4.0) placed around the lower right first molar for 1, 3, 7, and 14 consecutive days. The study comprised four groups: G1—control without EP; G2—animals with EP treated with water; G3—Losartan-treated animals (treatment started at the same day of EP induction), and G4—animals previously treated with Losartan for 30 days followed by induction of EP and continuity of treatment. Results: G2 rats had greater bone loss volume, increased number, and thickness and decreased separation of trabeculae. On the other hand, G4 animals showed significant improvements in these parameters. Histological analysis revealed that EP favors inflammatory cell infiltration and junctional epithelium, cementum with alveolar bone crest destruction, but animals pretreated with Losartan (G4) did not show these features. Although the G3 animals did not demonstrate the improvements detected in G4, mRNA expression results were similar. In mandibular tissue, EP promoted mRNA increases for ACE, AT1 receptor, and inflammatory mediators as well as decreases for antioxidant enzymes. However, Losartan treatments attenuated these responses in addition to promoting an increase in bone formation markers and transcription factors. Conclusion: AT1 receptor modulates EP progression.
Keywords: anti-inflammatory agents; antioxidant(s); bone biology; connective tissue biology; cytokine(s); experimental periodontitis; gene expression